The Effect of Quick Ratio and Debt to Ratio Assets Against Return on Assets - Asep Muhammad Lutfi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
This study aims to determine the effect of Quick Ratio and Debt to Asset Ratio on Return on Assets at PT. Garuda Indonesia Tbk. The method used was explanatory research with a sample of 85 respondents. Analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Quick Ratio did not significantly influence the Return on Assets of 34.3%, the hypothesis test obtained a significance of 0.127> 0.05. Debt to Asset Ratio has no significant effect on Return on Assets by 32.5%, the hypothesis test obtained significance of 0.140> 0.05. Quick Ratio and Debt to Asset Ratio simultaneously have a significant effect on Return on Assets by 37.9%, the hypothesis test obtained significance of 0.304> 0.05.